2019
DOI: 10.1016/j.cub.2019.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics and Morphological Reconstruction of Arcellinida Testate Amoebae Highlight Diversity of Microbial Eukaryotes in the Neoproterozoic

Abstract: Highlights d Arcellinida testate amoebae are comprised of seven major lineages d Reconstructed hypothetical ancestral states are congruent with Tonian fossils d Combined analysis of phylogenies and fossils suggest divergence as early as 730 mya

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(111 citation statements)
references
References 60 publications
9
93
3
Order By: Relevance
“…These VSMs-and others from comparably aged assemblages ca 789-729 Ma [35,36]-are interpreted as representing the oldest fossil evidence for arcellinid testate amoebae [37,38], which are abundant and diverse in modern freshwater and soil habitats, where they are largely bacterivorous and eukaryovorous [39][40][41]. Therefore, the VSMs themselves-with or without perforations-also serve as evidence for bacterivory and eukaryovory by ca 789 Ma [9,30,33,34,37,38]. The oldest evidence for biologically controlled eukaryotic biomineralization-the ca 810-million-year-old apatitic scale microfossils (ASMs) from the Fifteenmile Group in Yukon, Canada-has also been interpreted as indirect evidence for eukaryovory in the early Neoproterozoic [32,42].…”
Section: The Earliest Evidence For Eukaryotic Predation 21 Palaeontmentioning
confidence: 58%
See 1 more Smart Citation
“…These VSMs-and others from comparably aged assemblages ca 789-729 Ma [35,36]-are interpreted as representing the oldest fossil evidence for arcellinid testate amoebae [37,38], which are abundant and diverse in modern freshwater and soil habitats, where they are largely bacterivorous and eukaryovorous [39][40][41]. Therefore, the VSMs themselves-with or without perforations-also serve as evidence for bacterivory and eukaryovory by ca 789 Ma [9,30,33,34,37,38]. The oldest evidence for biologically controlled eukaryotic biomineralization-the ca 810-million-year-old apatitic scale microfossils (ASMs) from the Fifteenmile Group in Yukon, Canada-has also been interpreted as indirect evidence for eukaryovory in the early Neoproterozoic [32,42].…”
Section: The Earliest Evidence For Eukaryotic Predation 21 Palaeontmentioning
confidence: 58%
“…Similar perforations are also found in walls of younger organic-walled eukaryotic microfossils (the vase-shaped microfossils, or VSMs) from the 780 to 740 Ma Chuar Group, Grand Canyon, Arizona, USA [30,31], which are also widely interpreted as the direct result of eukaryovory [9,29,[32][33][34]. These VSMs-and others from comparably aged assemblages ca 789-729 Ma [35,36]-are interpreted as representing the oldest fossil evidence for arcellinid testate amoebae [37,38], which are abundant and diverse in modern freshwater and soil habitats, where they are largely bacterivorous and eukaryovorous [39][40][41]. Therefore, the VSMs themselves-with or without perforations-also serve as evidence for bacterivory and eukaryovory by ca 789 Ma [9,30,33,34,37,38].…”
Section: The Earliest Evidence For Eukaryotic Predation 21 Palaeontmentioning
confidence: 68%
“…An earlier phylogeny of 30 concatenated proteins, calibrated on an estimated divergence between the human and hydra lineages at 750 million years ago (mya), dates the split between the two major branches of Dictyostelia at 600 mya 11 . Many more genomes in both Opisthokonta and Amoebozoa, which together make up the Amorphea 13 have since then become available, as well as fossil dating of testate arcellinid amoebas within Amoebozoa 14,15 . To obtain a more accurate estimate of the divergence time of the two major branches of Dictyostelia, we inferred a novel phylogeny using 240 concatenated proteins across 85 species of Amorphea, and calibrated this phylogeny on fossil dating of www.nature.com/scientificreports www.nature.com/scientificreports/ divergence between major branches of testate amoebas, Fungi and Metazoa under relaxed molecular clock models (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is far from clear that the two taxa are directly related. First, it has been shown that the genus Hyalosphenia is paraphyletic, as H. papilio and H. elegans are only distantly related (Lahr et al, ; Lara, Heger, Ekelund, Lamentowicz, & Mitchell, ). Furthermore, a rough calculation can rule out the possibility of a very old age for H. papilio .…”
Section: Discussionmentioning
confidence: 99%